2014
DOI: 10.3171/2014.1.jns12392
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget, dual-electrode deep brain stimulation of the thalamus and subthalamic area for treatment of Holmes' tremor

Abstract: Object Holmes' tremor (HT) is generally considered to be a symptomatic tremor associated with lesions of the cerebellum, midbrain, or thalamus. Deep brain stimulation (DBS) therapy for essential tremor and parkinsonian tremor has proved quite successful. In contrast, surgical treatment outcomes for HT have often been disappointing. The use of 2 ipsilateral DBS electrodes implanted in parallel within the thalamus for severe essential tremor has been reported. Since dual-lead stimulation within a single target c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…All but one study reported no occurrence of AEs, and 1 study did not report AEs. Stimulation frequency ranged from 135 to 145 Hz, intensity was 2.0 V, and pulse width varied from 90 to 210 sec (Table 1) [21, 34, 38] .…”
Section: Resultsmentioning
confidence: 99%
“…All but one study reported no occurrence of AEs, and 1 study did not report AEs. Stimulation frequency ranged from 135 to 145 Hz, intensity was 2.0 V, and pulse width varied from 90 to 210 sec (Table 1) [21, 34, 38] .…”
Section: Resultsmentioning
confidence: 99%
“…Thalamic DBS has therefore often been applied for the surgical treatment of Holmes' tremor. 4) Treatment of Holmes' tremor should be individualized. A major goal is to keep the patient functioning independently as long as possible.…”
Section: Discussionmentioning
confidence: 99%
“… reported dual implantation of electrodes into the thalamus and STN and Kobayashi et al . conducted dual‐electrode DBS of the thalamus and subthalamic area with great Holmes tremor reduction.…”
Section: Potential Neurological Dbs Indicationsmentioning
confidence: 99%